The Mothering of Conduct Problem and Normal Children in Spain and the USA: Authoritarian and Permissive Asynchrony - Wahler, Robert G.; Cerezo, M. Angeles (The Spanish Journal of Psychology, 2005)
Ninety-two clinic-referred and nonclinical mother-child dyads in Spain and the USA were observed in their home settings under naturalistic conditions for a total of 477 hours. Children in the clinic-referred dyads were considered troubled because of conduct problems. The observations were aimed at assessing two forms of mother-child asynchrony, either of which was expected to differentiate clinic referred from nonclinical dyads. Authoritarian asynchrony was defined as a mother’s indiscriminate use of aversive reactions to her child, whereas the permissive form entailed indiscriminate positive reactions. Results showed the American mothers to generate more permissive asynchrony, whereas the Spanish mothers were inclined in the authoritarian direction. Only authoritarian asynchrony differentiated the clinical versus nonclinical dyads in each country. Discussion was centered on the greater salience of aversive as opposed to positive maternal attention, and cultural differences between countries that might have accounted for the different parenting styles.